ANALISIS KINERJA KEUANGAN CV. ABC DENGAN PENDEKATAN RASIO PROFITABILITAS,LIKUIDITAS DAN SOLVABILITAS TAHUN 2021-2022 - Hidayat, Muhammad; Suci, Rama Gita (Komunitas Manajemen Kompetitif, 2023)
Abstrak : The company's financial performance can be assessed by analyzing financial ratios. Financial ratios can consist of several groups such as profitability, liquidity and solvency ratios. This study uses secondary data obtained indirectly from the results of CV ABC's financial statements for 2021-2022 using profitability ratios (Return On Assets, Return On Equity, Gross Profit Margin and Net Profit Margin), liquidity ratios (Current Ratio, Quick Ratio, and Cash Ratio) and solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio). This research uses quantitative methods with a descriptive analysis model that aims to analyze financial ratios so that after analysis the company can know and can assess financial performance based on the value of the company's financial ratios. Based on the results of the study that the results of the assessment of financial performance on CV ABC have increased quite well. The profitability ratio can be said to be in good condition, so that the results of the ROA analysis meet the company's performance measurement standards, the results of the ROE analysis are good, the GPM results are quite good in 2021 and less good based on the 2022 analysis and the NPM analysis is not good for the last two years. in the Quick Ratio analysis it is said to be less good in 2021 and quite good in 2022, in the Cash Ratio analysis it is said to be not good for the last 2 years.then in the solvency analysis it is said to be good and has increased over the last two years based on the results of the analysis of Debt to Asset Ratio and Debt to Equity Ratio). Abstrak : The company's financial performance can be assessed by analyzing financial ratios. Financial ratios can consist of several groups such as profitability, liquidity and solvency ratios. This study uses secondary data obtained indirectly from the results of CV ABC's financial statements for 2021-2022 using profitability ratios (Return On Assets, Return On Equity, Gross Profit Margin and Net Profit Margin), liquidity ratios (Current Ratio, Quick Ratio, and Cash Ratio) and solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio). This research uses quantitative methods with a descriptive analysis model that aims to analyze financial ratios so that after analysis the company can know and can assess financial performance based on the value of the company's financial ratios. Based on the results of the study that the results of the assessment of financial performance on CV ABC have increased quite well. The profitability ratio can be said to be in good condition, so that the results of the ROA analysis meet the company's performance measurement standards, the results of the ROE analysis are good, the GPM results are quite good in 2021 and less good based on the 2022 analysis and the NPM analysis is not good for the last two years. in the Quick Ratio analysis it is said to be less good in 2021 and quite good in 2022, in the Cash Ratio analysis it is said to be not good for the last 2 years.then in the solvency analysis it is said to be good and has increased over the last two years based on the results of the analysis of Debt to Asset Ratio and Debt to Equity Ratio).